The night she disappeared : a novel - Jewell, Lisa (New York : Atria Books, 2021)
On a beautiful summer night in a charming English suburb, a young woman and her boyfriend disappear after partying at the massive country estate of a new college friend. One year later, a writer moves into a cottage on the edge of the woods that border the same estate. Known locally as the Dark Place, the dense forest is the writer's favorite area for long walks and it's on one such walk that she stumbles upon a mysterious note that simply reads, "DIG HERE." Could this be a clue towards what has happened to the missing young couple? And what exactly is buried in this haunted ground?
Originally published in Great Britain in 2021 by Century.
Keywords: Missing persons -- Fiction; Authors -- Fiction; Forests and forestry -- Fiction; Psychological fiction; Thrillers (Fiction)